Study on chemical constituents of the lichen Parmotrema tinctorum (Nyl.) Hale - Tram, Nguyen Thi Thu; Huyen, Vu Thi; Pascal, Retailleau (Vietnam Journal of Science and Technology, 2018)
A phytochemical investigation was conducted on a foliose lichen, Parmotrema tinctorum (Nyl.) Hale, collected in Lam Dong province, Vietnam. Colour reactions for identification of lichen substances (+K deep yellow, +C red, +KC red, + P pale yellow) suggested the presence of atranorin, lecanoric acid, quinones, depsides, and xanthones containing two free hydroxyl groups in meta-position. Chemical constituent study led to the isolation of six compounds, including atranol (1), methyl haematomate (2), divaricatinic acid (3), methyl divaricatinate (4), atranorin (5) and lecanoric acid (6). Their structures were confirmed unambiguously by X-ray diffraction, spectroscopic data and compared with those in references.